Do you really understand? Achieving accuracy in interracial relationships. [article]. - Holoien, Deborah Son; Bergsieker, Hilary B.; Shelton, J. Nicole; Alegre, Jan Marie
Accurately perceiving whether interaction partners feel understood is important for developing intimate relationships and maintaining smooth interpersonal exchanges. During interracial interactions, when are whites and racial minorities likely to accurately perceive how understood cross-race-partners feel? We propose that participants race, desire to affiliate, and racial salience moderate accuracy in interracial interactions. Examination of cross-race roommates (Study 1) and interracial interactions with strangers (Study 2) revealed that when race is salient, Whites higher in desire to affiliate with racial minorities failed to accurately perceive the extent to which racial minority partners felt understood. Thus, although the desire to affiliate may appear beneficial, it may interfere with whites? ability to accurately perceived how understood racial minorities feel. By contrast, racial minorities higher in desire to affiliate with whites accurately perceived how understood white partners felt. Furthermore, participants? overestimation of how well they understood partners correlated negatively with partners? reports of relationship quality. Collectively, these findings indicate that racial salience and desire to affiliate moderate accurate perceptions of cross-race partners-even in the context of sustained interracial relationships-yielding divergent outcomes for whites and racial minorities. - - (from the author)